DEVELOPING ACADEMIC WRITING IN A BUSINESS ORIENTED UNIVERSITY - Foley, Joseph (Universitas Pendidikan Indonesia, 2013)
Abstract: This research investigated the development of language choices in the Academic writing of students at an English medium university in Thailand. The first part involved looking at the writing in the first semester of their English program at the university. representing the level of the studentsâ€™ writing on entry into the university. Seventy two samples of first year studentsâ€™ writing were collected, but only 12 were randomly selected for this study in order to compare their progress over a period of 14 weeks (first semester). The second part of the research looked at the writing of studentsâ€™ journals at the end of their second semester of their first year after the implementation of a writing program based on research originally developed in Australia (Derewianka, 2003). A third part of the research investigated the development of studentsâ€™ writing towards the third year in university with specific reference to their academic writing in the business English program. The focus on Business English was mainly because the university was well known in this field of study. The framework for the analysis of the studentsâ€™ writing was based on a systemic functional approach (Halliday andÂ Matthiessen, 2004). In order to provide insights into the meaning and effectiveness of the text, a discourse grammar needs to be functional and semantic in its orientation. This paper discusses the development of the Nominal Group (NG) in the studentsâ€™ writing in THEME position, as this was felt to be a major issue in the development of academic discourse. However NGs in the RHEME would also be looked, as this was a part of the text structure, where complex nominal groups would be expected as part of the NEW information. Â The resulting analysis showed that initially the students had a limited knowledge of the different genres and used an equally limited range of lexical and grammatical choices. After the implementation of a new teaching approach in the second semester of the first year, some improvement could be observed. During the third year of the English program, improvement in the writing of genres used in â€œbusinessâ€ writing, such as Reports, was clearly evident.